Bitumen-based plastitar: a novel plastic form variant in terrestrial environments - Ehlers, Sonja M.; Ellrich, Julius A. (Frontiers in Environmental Science, 2024)
Plastitar has recently been reported in marine environments worldwide. Plastitar is plastic embedded in crude oil residues. This plastic form, i.e., geochemically or -physically altered plastic, has been proposed to derive from water motion driven plastic-crude oil-interactions in pelagic and benthic habitats. In this study, we introduce bitumen-based plastitar: a novel plastic form variant that we detected in supra-intertidal marina walls, riverbank cobblestone pavements, and roads. Fourier-transform infrared (FTIR) spectroscopy identified plastic fragments, bottle cap plastic liners, and paint chips, that we had found firmly embedded in black joint sealant, as polypropylene, polyethylene, polyester epoxide and alkyd varnish. Field observations, pyrolysis-gas chromatography / mass spectroscopy (PY-GC/MS) and FTIR indicated that the black joint sealant consisted of a bitumen-mineral-mixture that is commonly used as adhesive and filler in hydraulic engineering and road construction. Brittle plastic fragments showed signs of melting such as bubbles, holes and melt inclusions and, therefore, constituted pyroplastics, i.e., incompletely combusted and melted plastics with rock-like appearances. Bottle caps and paint chips were deeply pressed into the joint sealant. These findings indicate that bitumen-based plastitar is formed by plastic being (un)intentionally included into heated liquid bitumen or pressed into hardened bitumen. Our field inspections detected that bitumen-based plastitar degraded by up to 66 % over 608 days releasing microplastics (plastics < 0.5 cm) into the environment. Overall, our study shows, for the first time, that plastitar variants can form from materials other than crude oil residues and in terrestrial environments. We hope that our study will increase the awareness for these novel plastic fixation processes, i.e., plastic agglomeration with bitumen through heat and pressure, which could help to prevent plastitar formation during future construction works.